A Study on Adoption of Mobile Learning Apps (MLA) : Development of an Integrated Framework in a Multinational Context - Dash, Ganesh; Akmal, Syed; Chakraborty, Debarun (Indian Journal of Marketing, 2023)
Purpose: In this study, we provided an integrated framework to assess the determinants of intention to adopt and recommend mobile learning apps (MLA) in an emerging economy context. Methodology: We integrated diffusion of innovation (DOI) & DeLone and McLean’s information systems success model (D&M ISS Model). Four independent measures, compatibility, complexity, system quality, and information quality, were taken from the mentioned theories. Intention to adopt and intention to recommend are the dependent constructs. Intention to adopt also plays the role of mediator. Three hundred seventy-two participants from Saudi Arabia and India were included in the survey. Partial least squares (PLS) structural equation modeling (SEM) was used for the analysis. Findings: The results suggested that all the antecedents influenced the intention to adopt and recommend except for compatibility. Compatibility affected adoption intention only. The intention to adopt had a substantial impact on the recommendation intention. It also successfully mediated all the proposed relationships. In addition, a multi-group analysis (MGA) was also conducted to have country-specific results. Originality: We provided a new, comprehensive, and integrated model to assist learning app companies in implementing new technology. Two significant theories were integrated to provide a holistic and futuristic framework.